The Effect of Debate Technique to Students’ Speaking Ability - Fatmawati Laisouw (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This research was conducted to study the effect of debate technique used in the speaking classroom. By so doing, this researcher expected that this research provided more information about the availability of using this technique to teach speaking, especially English speaking. This research involved 30 students at English Education Program in STKIP Kie Raha of Ternate. Tests (pre and posttest) were administered and also interview. Based on the data, it is found that there is significant difference between before and after the treatment. Although it is noted that most students still had less vocabulary and less self-confidence to talkative in the debate, the test scores showed that Debate Technique is available to be considered in teaching speaking.